Comparison of growth performance and biochemical components between parent and hybrid offspring in the oriental river prawn, Macrobrachium nipponense. (27th January 2021) - Li, Yiming; Jiang, Qichen; Chen, Qiang; Liu, Zhiquan; Huang, Yinying; Tian, Jiangtao; Huang, Youhui; Zhao, Yunlong
Summary: Macrobrachium nipponense, as one of the large‐yield farmed shrimp, is facing germplasm degradation. Genetic improvement through hybridization is one of the effective methods to solve this problem. In this study, using a three‐line hybrid strategy, two‐hybrid F1 populations were obtained using three local populations of M. nipponense as parents for crossbreeding. Five populations were then cultured for 3 months. Growth rate performance was measured by the hepatosomatic index, weight gain, body length growth rate and special growth rate. Biochemical components were also assessed. The results showed that the survival rate and growth performance of the hybrid progeny were better than those of the parents. The levels of triglycerides, total cholesterol, glycogen and lactic acid of the hybrid population were higher than those of the parents. This was consistent with variation in the activity of four digestive enzymes. Compared with the results of the fatty acid and amino acid analysis, it was found that the contents of polyunsaturated fatty acids such as eicosapentaenoic acid, docosapentaenoic acid and docosahexaenoic acid and eight essential amino acids in the hybrid populations were significantly higher than those of their parents, and the contents of flavor amino acids were higher. The expression level of molting genes related to the growth of the parent populations was lower than that of the hybrids. These results show that crossbreeding is effective for the genetic improvement of M. nipponense germplasm. Hybrids showed advantages in growth and nutrition and multigenerational breeding will be required to form a stable germplasm.